PENEROBOSAN TERHADAP BATAS-BATAS KEBEBASAN KEKUASAAN KEHAKIMAN - I Gusti Ketut Ariawan (Faculty of Law, Universitas Diponegoro, 2010)
Question of free Judicial Power are deemed completed when there is agreement (consensus) of the scientific principle of freedom of the judiciary, which is universal, because it has been accepted through the doctrine and constitution. Scientific consensus on the freedom of judiciary actually don't do discourse or legal discourse is stopped at one point, but in fact it triggers a new discourse that is abuse of the freedom of judicial power. Misuse ofpoweris manifested in the form of arbitrariness on the part of the Supreme Court in the form of creating